The Influence of Good Corporate Governance Mechanisms On The Profitability of State-Owned Banking - Marsanda, Marsanda; Susilowati, Dwi; Moorcy, Nadi Hernadi (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to analyze the influence of good corporate governance mechanisms on state-owned banking companies. The variables in this study are the Board of Commissioners, Board of Directors, Audit Committee, and Institutional Ownership. The number of samples in this study is 39. The analysis method used is multiple linear analysis using the SPSS (Statistical Product and Services Solutions) version 25 program. The results of the study indicate that the variables of the Board of Commissioners, Board of Directors, and Audit Committee have a positive and insignificant effect on ROA, the variable of Institutional Ownership has a positive and significant effect on ROA.